2017
DOI: 10.1080/13880209.2017.1304427
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Buchenavia tetraphylla against Candida albicans strains isolated from vaginal secretions

Abstract: Buchenavia tetraphylla methanolic extract (BTME) is a great source of antimicrobial compounds that are able to enhance the action of fluconazole against different C. albicans strains; this action seems related to inhibition of cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(43 reference statements)
0
8
0
Order By: Relevance
“… Cavalcanti Filho et al (2017) verified that the methanolic extract of Buchenavia tetraphylla is a great source of antimicrobial compounds that enhance the action of FLZ against different C. albicans isolates from vaginal secretions as well as azole-resistant isolates. The extract increased the action of FLZ in most strains through additive (20% of strains) or synergistic (60% of strains) effects.…”
Section: Peptides As Antifungal Agentsmentioning
confidence: 77%
“… Cavalcanti Filho et al (2017) verified that the methanolic extract of Buchenavia tetraphylla is a great source of antimicrobial compounds that enhance the action of FLZ against different C. albicans isolates from vaginal secretions as well as azole-resistant isolates. The extract increased the action of FLZ in most strains through additive (20% of strains) or synergistic (60% of strains) effects.…”
Section: Peptides As Antifungal Agentsmentioning
confidence: 77%
“…Herein, we report the selection of high antioxidant fractions from B. tetraphylla leaf extracts using in vitro and in vivo approaches. Products derived from this plant have been shown as potential candidates for the development of new antimicrobial agents [20][21][22]; however, their antioxidant actions have not been properly addressed. The in vitro results obtained in this study showed that the methanolic extract (BTME) had a higher antioxidant activity, and this effect was correlated with its higher phenolic and flavonoid content.…”
Section: Discussionmentioning
confidence: 99%
“…B. tetraphylla is popularly known as "tanimbuca" in Brazil, where it has ethnomedicinal importance for communities in the northeast region [19]. It is also known to have a broad spectrum of antimicrobial activity, inhibiting bacteria, fungi, and virus [20][21][22]. Buchenavianine and two derivatives (O-demethylbuchenavianine, N,O-bis-(demethyl)buchenavianine) have been isolated from B. tetraphylla.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest concentration, at which no color change occurred, was taken as the MIC. Afterward, cultures were seeded in SDA plates, incubated for 48 h at 30 º C, and consequently minimum fungicidal concentration (MFC) was determined [20].…”
Section: Methodsmentioning
confidence: 99%